Edukasi Skrining dan Monitoring Hipertensi pada Usia Dewasa di Posyandu Desa Tengah - Massatriadi Massatriadi; Dharina Baharuddin; Radhiah Zakaria (Yayasan Literasi Sains Indonesia, 2026)
Hypertension is a major non-communicable disease and a public health concern because it often occurs without early symptoms but may cause serious complications such as cardiovascular disease, stroke, and kidney failure. Low public awareness regarding routine blood pressure screening contributes to the increasing risk of uncontrolled hypertension. This activity aimed to improve adults’ knowledge and awareness about the importance of hypertension screening and monitoring at Posyandu Desa Tengah.The study used an evaluation research design with the CIPP (Context, Input, Process, Product) approach. The population included healthcare workers, hypertensive patients, and program documents, with data collected through interviews, observations, document reviews, and medical records. The instruments used were the MMAS-8 questionnaire and clinical measurement tools. Data were analyzed using quantitative, qualitative, and benchmarking methods.The results showed an increase in participants’ knowledge regarding hypertension risk factors, prevention, early detection, and the importance of regular blood pressure monitoring. Several participants who previously did not know their blood pressure status were identified as having elevated blood pressure and received education and recommendations for further medical follow-up. The program also increased community awareness of healthy lifestyle practices and regular blood pressure checks. In conclusion, hypertension screening and monitoring education at Posyandu Desa Tengah was effective in improving knowledge, awareness, and community participation in hypertension prevention and control. Continuous implementation of education and screening activities through collaboration among healthcare workers, health cadres, and families is recommended to support early detection and effective hypertension management.